Design and investigation of air-cooled heat sinks using 3D printing technology - Lim, Ming Chong (2016)
This study presents the heat transfer performance of five pin fin heat sinks that have been fabricated using Selective Laser Melting. The five heat sinks vary in their pin fin cross-section, with two common designs, the circular pin fin and rounded rectangular cross-section pin fin, and three novel designs which consist of a NACA-0024, a NACA-4424 and also a NACA-4424 rotated at a 5° angle of attack. Fabrication of the pin fins showed that SLM was able to produce the intricate details accurately with a maximum dimensional error of 2.5%. The experimental results of the various fins were compared and the rounded rectangular cross-section fin was determined to have performed the best showing up to 35% enhancement as compared to the circular pin fin. While the aerofoil cross-section shapes showed similar enhancement of up to 35% enhancement as compared to the circular pin fin at low Reynolds number, enhancement effects were less prominent at higher Reynold numbers. Variation in symmetry showed that symmetrical aerofoil performed better and the difference in performance was increasingly obvious at higher Reynolds number. The angle of attack did not show any effect on the Nusselt numbers calculated. This was a result of the small angle of attack used in the conduct of experiments. In all, the aerofoil designs with small angle of attack are not suitable for use in a flow with bypass as it did not show any significant improvements over the common existing designs.